CONSTRUCTION DESIGN FOR 4.5 BAR WATER TUBE TYPE BOILER USING SOLIDWORKS 2018 SOFTWARE - Ariyanto Ariyanto (International Journal Science and Technology, 2022)
Distillation or simple distillation uses the principle of separating two or more liquids based on differences in the boiling points of each component. The distillation process itself has two main stages, namely the evaporation stage and the condensation or condensation stage. Therefore, distillation equipment uses a heating device in the form of a boiler and a cooler in the form of a heat exchanger. In the refining process, the heart of the distillation system lies in the boiler as a steam producing component. Therefore, the effectiveness of the boiler to produce saturated steam greatly determines the results of the refining process. To determine the power of the boiler, it is necessary to analyze the Boiler simulation calculations which include Von misses, displacement and safety factor simulations. The simulation is carried out at a pressure of 4.5 Bar which produces a Von misses max value. of 3.444 MPa, with the highest displacement value of 0.002 mm and the smallest value of 0 mm, and produces a safety factor value of 75. With this safety factor value, it can be said that the frame construction is safe.